The Effect of an Android-Based HIV/AIDS Monitoring Application on Adolescents’ Knowledge and HIV/AIDS Screening - Maulidiyah Salim; Elma Marsita; Tessa Siswina (MEDICA (International Medical Scientific Journal), 2026)
Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) remain major global public health challenges, including in Indonesia, where adolescents are particularly vulnerable due to high-risk behaviors. This study aimed to evaluate the effectiveness of an Android-based HIV/AIDS monitoring application (PAHIVA) in improving adolescents’ knowledge and facilitating early HIV/AIDS risk screening. A pre-experimental study with a one-group pretest–posttest design was conducted among 90 high school students in Singkawang City. Data on HIV/AIDS knowledge were collected using structured questionnaires before and after the intervention and analyzed using the Wilcoxon signed-rank test. The results showed a statistically significant increase in knowledge scores, with the median rising from 67 at baseline to 87 after the intervention (p < 0.001). A total of 76 participants demonstrated improved knowledge, while 14 showed no change. Additionally, the application-based screening identified 9 participants (10%) as being at high risk for HIV/AIDS, who were subsequently referred to the nearest Voluntary Counseling and Testing (VCT) clinic for further evaluation. In conclusion, the PAHIVA application was associated with improved knowledge and demonstrated potential as a preliminary HIV/AIDS risk screening tool among adolescents. This mobile health innovation may contribute to strengthening adolescent-focused HIV/AIDS prevention strategies, although further studies with more robust designs are recommended to confirm its effectiveness.